Chromathographic studies on essential oils from cinnamomum SPP - Roslina, binti Razak. (Universiti Malaysia Sarawak (UNIMAS), 2004)
The chemical composition of the leaves, stem bark and roots essential oils of Cinnamomum A and Cinnamomum B collected from Semantan, were analysed by GCI FID and GC-MS. Cinnamomum A were found to contain essential oils 1.40%, 2.98% and 2.37% from its leaves, stem bark and root, respectively. Cinnamomum B consisted with 1.22%, 0.95% and 1.46% essential oil from its leaves, stem bark and root, respectively. Both species were contained abundant of monoterpenoids and sesquiterpenoids. g-selinene, b-caryophyUene, (+)-(Z)-methyl epijasmonate, 4-hydroxycinnamic acid, hexyl octanoate, are the major components of Cinnamomum A essential oil. On the other hand, Cinnamomum B consists of cinnamic acid, camphor, 4-acetylmethylcyclohexane, geranylacetone and b-selinene as the major essential oil composition.